Adaptive packet selection scheme and selective retransmission algorithm for Bluetooth - WANG Xue; QIAN Zhi-hong; LI Bing; LI Yue (Tongxin xuebao, 2011)
To improve the anti-jamming capability and transmission efficiency of Bluetooth,the retransmission mecha-nism was worked out for baseband layer and L2CAP layer.In baseband layer,the adaptive packet selection strategy was presented,which utilized the times of retransmission to evaluate the channel quality.The packet that satisfied the biggest throughput of the current channel was chosen dynamically according to the times of retransmission.In L2CAP layer,in view of the shortcomings that data frames successfully received need to be transmitted once more,the selective retrans-mission algorithm was proposed,depending on the unique characteristic that Bluetooth could support a number of logical channels.The algorithm combines the retransmission mode and flow control mode,with no redundancy varieties of the protocol.Simulations and performance analysis indicate that system throughput and transmission efficiency get promoted with decrease of communication delay.It is easy to implement the algorithm.